HIV negative aids-idiopathic CD4 lyphocytopenia - Ashima Bali Behl; Puneeta Vohra; Vikram Bali (Wolters Kluwer Medknow Publications, 2018)
Idiopathic CD4+ T-cell lymphocytopenia (ICL) is a rare disorder of immune system with heterogeneous clinical manifestations and immunologic profile. This is a rare condition, which was first defined in 1992 by the Centers for Disease Control and Prevention. It is marked by a CD4 count that is <300 cells/mm3 without human immunodeficiency virus (HIV) infection. Its course differs from that of acquired immunodeficiency syndrome (AIDS), although patients with this disorder may develop opportunistic infections. Hence, the clinicians should be aware of this rare immunologic disorder and that a decrease in the CD4 count is not a hallmark for HIV infection, but could be due to other idiopathic causes as well.